Regional structure of wages and external economies in Spain - Raul Ramos; Esteban Sanroma (European Regional Science Association (ERSA), 1998)
Regional data on wages for the Spanish Economy show that workers who live in developed regions earn more than workers in other regions. For example, the average wage in Madrid or in Catalonia -two of the most developed regions- is about a 50% higher than in Murcia -a region specialised in agriculture with low levels of per capita income-. New Economic Geography models, such as Krugman (1991), provide a possible explanation of why firms do not move from these regions to others where wages were lower. These kind of models describe how firms concentrate their production in one location due to the existence of increasing returns to scale and low transport costs in the presence of pecuniary external economies. Previous studies for the Spanish Economy use aggregate data to explain why average wages in the same sector are different across regions. The original contribution of this paper consists of using individual data on wages from the Encuesta de Presupuestos Familiares -carried out by the Instituto Nacional de Estadistica with reference to the years 1990-1991- to detect the existence and the nature of external economies. This information permits to control the influence of individual (gender, age, level of studies) and job (occupation, industry, full or part-time work) characteristics on wages to, first, detect the existence of external economies and, second, test alternative explanations of their presence: for example, the size of the labour market, the accumulation of the same kind of qualified workers or the geographical specialisation in a dominant manufacturing activity.
Keywords: 330